2007
DOI: 10.1345/aph.1h680
|View full text |Cite
|
Sign up to set email alerts
|

“Insight” into Drug Quality: Comparison of Simvastatin Tablets from the US and Canada Obtained via the Internet

Abstract: Results of this study suggest comparable quality assurance manufacturing standards for the US innovator product and the Canadian generic drug products tested. These findings have clinical, legal, and economic implications that should be addressed by policy makers to safeguard consumers who choose to purchase Canadian-manufactured drugs via the Internet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…A GAO study of 68 samples of 11 prescription drugs, including sertraline, found that the chemical compositions of all the Canadian samples were comparable to the FDA-approved product (GAO, 2004). In another study, generic simvastatin from Canada was not significantly different than the US brand product (Veronin et al, 2007). However, users of online pharmacies should be aware that even CIPA members may offer formulations that were not evaluated and approved by the FDA, such as the generic quetiapine XR.…”
Section: Discussionmentioning
confidence: 94%
“…A GAO study of 68 samples of 11 prescription drugs, including sertraline, found that the chemical compositions of all the Canadian samples were comparable to the FDA-approved product (GAO, 2004). In another study, generic simvastatin from Canada was not significantly different than the US brand product (Veronin et al, 2007). However, users of online pharmacies should be aware that even CIPA members may offer formulations that were not evaluated and approved by the FDA, such as the generic quetiapine XR.…”
Section: Discussionmentioning
confidence: 94%
“…Online pharmacy samples varied hugely in size, from 4 [83,94,95] to 5859 [10]. The sample selection had different inclusion criteria: many studies focused on online pharmacies selling numerous kinds of drugs, while others selected online pharmacies offering a single medication or 1 class; some selected only online pharmacies not asking for a prescription, and others only online pharmacies based in specific countries.…”
Section: Resultsmentioning
confidence: 99%
“…Online pharmacies were most frequently based in the United States in virtually all the studies that investigated samples that were not restricted geographically [10,57,60,61,62,66,73,84]. Other studies focused on online pharmacies based in specific countries, such as the United States [87,88,95], the United States and Europe [27], the United States and Canada [89], Canada [94], or Brazil [92]. Some researchers looked for where the websites were registered, and they found the United States to be the most frequent location of domain registration [10,67,68,84,93].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations